LOW ARABIC LITERACY CONTRIBUTES TO MISUNDERSTANDING OF ISLAMIC BANKING CONCEPTS IN RURAL INDONESIA - Naidin Syamsuddin; Syamsiar Guntur; Najwa Awaliyah Aidin (Al Ibrah: Journal of Arabic Language Education, 2026)
This study examines how low Arabic literacy contributes to the misunderstanding of Islamic banking concepts in rural Indonesia. The research addresses the gap between the growth of Islamic financial institutions and the limited public understanding of key Arabic-based financial terminology. The objective of this study is to analyze the role of Arabic literacy in shaping conceptual understanding and influencing the adoption of Islamic banking services. A qualitative descriptive approach was employed, involving in-depth interviews, participant observation, and document analysis among rural community members. The findings reveal that most participants rely on informal sources of information, such as family and social networks, rather than structured educational channels. Limited familiarity with Arabic terms such as akad, mudharabah, and riba leads to misconceptions, including the belief that Islamic banking is exclusively for Muslims. These misunderstandings contribute to a preference for conventional banking services due to greater accessibility and familiarity. Additionally, minimal educational outreach from Islamic banking institutions further limits public exposure to accurate conceptual explanations. The study concludes that Arabic literacy plays a critical role in shaping financial understanding and behavior. Integrating Arabic language learning into financial literacy programs is essential to improve comprehension and promote inclusive access to Islamic banking services.